Blade drag factor - Kleshnev, V. (BioRow, 2018)
During the drive phase, the blade slips through the water creating a resistive drag force, which is in fact the propulsive force moving the whole rower-boat system forward. The lower the slippage of the blade, the higher its propulsive efficiency. However, the latter depends on the boat`s velocity (RBN 2012/06), which varies depending on boat types, weather conditions and during the stroke cycle and makes its evaluation difficult. So, we proposed to evaluate blade work using a method similar to boat shell Drag Factor DF. Thera are at least three options available, which use various reference systems.